THE EFFECT OF AUDITOR INDEPENDENCE, EXPERIENCE, AND ACCOUNTABILITY ON AUDIT QUALITY (THE PUBLIC ACCOUNTANT OFFICE IN PALEMBANG CITY) - Hadli Hadli; Wahyu Satria; Ikraam Ikraam (Jurnal Manajemen, 2022)
This research aims to know the influence of the independence, the experience and the accountability to quality audits on public accountant in Palembang. Collecting samples in study using census method. Data collected by distributing questionnaries to 10 public accountant in Palembang, and only 6 public accountant willing to fill out the questionnaire. As many as 44 sheets and 39 sheets of questionnaires back. This research using SPSS version 25 for analyzing the data. The variables used in this study is composed of variabel dependent namely, the quality audit (Y), and the independent variables namely, the independence (X1), the experience (X2), and the accountability (X3). Based on the results of the test t significance level, indicating that the independence 0,003 < 0,05, experience 0,003 < 0,05 dan accountability auditor 0,578 > 0,05. The results of this research is the independence and experience auditor positive effect to the quality audit on publik accountant in Palembang, while the accountability of the auditor has no effect to the quality of the audit on publik accountant in Palembang.